Finite element modelling and diffraction measurement of elastic strains during tensile deformation of HCP polycrystals - Song, X; Zhang, S; Dini, D; Korsunsky, A (2008)
In this paper a 3D, elastically anisotropic crystal-plasticity based constitutive model is used to describe cyclic deformation and hardening of polycrystalline HCP (hexagonal close-packed) materials. A diffraction post-processor is developed to allow critical assessment of model predictions against XRD data. Model results for titanium alloy Ti-6Al-4V are compared with synchrotron high energy X-ray polycrystalline diffraction data. The significance of elastic anisotropy and three-dimensionality of the model is discussed. © 2008 Elsevier B.V. All rights reserved.